2020
DOI: 10.1039/d0fo00971g
|View full text |Cite
|
Sign up to set email alerts
|

Identification and molecular docking study of fish roe-derived peptides as potent BACE 1, AChE, and BChE inhibitors

Abstract: Acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and beta-secretase 1 (BACE 1) play vital roles in the development and progression of Alzheimer's disease (AD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…Thus, unknown tri‐ and tetra‐peptides were selected for research. Moreover, bioactive peptides could be released by enzymatic hydrolysis and exhibited various regulatory effects such as antihypertensive, 13 antioxidative, 14 immune defense, 15 anti‐Alzheimer's disease, 16 and opioid effects 17 . Meanwhile, bioactive peptides with high XO inhibitory activity have also attracted much attention in recent years, in studies of the hydrolysates of shark cartilage protein, 12 walnut protein, 18 tuna protein, 19 and bonito protein 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, unknown tri‐ and tetra‐peptides were selected for research. Moreover, bioactive peptides could be released by enzymatic hydrolysis and exhibited various regulatory effects such as antihypertensive, 13 antioxidative, 14 immune defense, 15 anti‐Alzheimer's disease, 16 and opioid effects 17 . Meanwhile, bioactive peptides with high XO inhibitory activity have also attracted much attention in recent years, in studies of the hydrolysates of shark cartilage protein, 12 walnut protein, 18 tuna protein, 19 and bonito protein 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The main weakness of the traditional method is that it is time consuming and suffers from sensitivity reduction. In silico gastrointestinal (GI) digestion and hierarchical virtual screening might be more valid methods to substitute for the classical enzymatic hydrolysis method 16 …”
Section: Introductionmentioning
confidence: 99%
“…ACE inhibitory peptides have been identified from a wide range of food proteins, such as Antarctic krill (Ji et al., 2017), seaweed (Admassu et al., 2018), olive seeds (Esteve et al., 2015), green soybeans (Hanafi et al., 2018), and Chlorella vulgaris (Xie et al., 2018). Among them, short chain peptides like tripeptides are point of focus, as they are predicted to be easily absorbed into the blood circulatory system, and less affected by gastrointestinal digestion (Martin & Deussen, 2017; Yu et al., 2020). Based on structure–activity analysis, several characteristics of the identified ACE inhibitory peptides have been found.…”
Section: Introductionmentioning
confidence: 99%
“…( Nongonierma, Mooney, Shields, & Fitzgerald, 2013 ). Many studies have confirmed the reliability of in silico screening methods, which can be regarded as valid alternatives to classic methods ( Fu et al, 2016 , Yu et al, 2020 , Yu et al, 2020 , Zhao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 98%